Farmers' Motivation to Fund Children's Education Amidst Income Uncertainty in Rural Environments - Intan Siti Masitoh; Yoga Prima Putra; AIsha Nadia (Journal of Future Education, 2025)
This study aims to analyze farmers' motivations for financing their children's education amidst income uncertainty in rural areas. The focus of the study is on understanding the values, beliefs, and strategies used by farmers to maintain the continuity of their children's education despite facing economic constraints and income fluctuations. This study employed a qualitative, descriptive approach. Data were collected through in-depth interviews with farmers with school-age children in rural areas. The data sources consisted of primary data obtained directly from informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, linking field findings to Maslow's motivational theory and the Hoover-Dempsey & Sandler model of parental involvement. The results indicate that farmers' motivation to finance their children's education is driven by the belief that education is a basic need and a long-term investment for their children's future. Income uncertainty is not a major obstacle as long as farmers possess intrinsic motivation, sound financial planning, and a strong commitment to their children's education. The conclusions of this study confirm that the continuity of farmers' children's education is more influenced by the values, motivation, and active role of parents than by economic conditions alone.